Liver transplantation for Gaucher disease presenting as neonatal cholestasis: Case report and literature review. (23rd April 2020) - Soudek, Lucy; Siddiqui, Iram; Guerin, Andrea; Sondheimer, Neal; Inbar‐Feigenberg, Michal; Abuquteish, Dua; Walia, Jagdeep S.; Kamath, Binita M.; Kehar, Mohit
Abstract: Background: We present a rare case of neonatal cholestasis in a female infant with Gaucher Disease (GD), who received liver transplantation. We review the relevant literature on similar disease presentations. Methods: A chart review of the index case was performed. PubMed and Medline databases were searched to identify other cases. Results: A 4‐day‐old female was referred with conjugated hyperbilirubinemia. Physical examination revealed icterus with hepatosplenomegaly and normal neurologic examination. The diagnosis of GD was confirmed through liver biopsy, low glucocerebrosidase enzyme activity, and two pathogenic mutations in GBA gene. Despite early initiation of ERT, the patient had worsening of her liver failure and underwent a left lateral segment liver transplant from a living donor at 7 months of age. She experienced improvement of her liver enzymes and coagulation, but passed away at 8 months due to the late onset of neurologic involvement. Nine other cases of GD presenting with neonatal cholestasis have been reported. Forty‐four percent (4/9) of cases received ERT and none were considered for transplant. Overall, the literature suggests a poor prognosis with death reported in 77% (7/9) cases. Conclusions: Neonatal presentation of GD represents a poor prognosis despite early initiation of treatment. Diagnosis remains a challenge as the presentation is rare and multiple tests such as BM biopsy, liver biopsy with both light and electron microscopy, enzymology, and genetic testing may need to be completed to reach a diagnosis. Neurological sequelae may manifest later making the decision to proceed with liver transplantation a difficult one.